Impact of Single-Parent Households on Child Educational Attainment in Suburban Areas - Ernawatiy Ernawatiy (Generasi Sains Indonesia, 2024)
This study explores how unmarried-parent families affect the infant education achievement in the suburbs. Due to a qualitative research approach, data had been collected through semi-structured interviews with dad and mom, teachers, and pupils of many suburban schools. The results indicate large financial, emotional, and psychological strains that they face through children in single parent households and they take a toll on them in terms of academic achievement. In spite of these difficulties, the observe shows the importance of parental participation, strong faculty support, and network involvement as a means of reducing the negative outcomes and enhancing the beneficial ones. The study highlights the desire to have full-fledged help mechanisms and policies that address the specific needs of unmarried-determine families to enhance academic equity.